Optimal selection of long time acoustic features using GA for the assessment of vocal fold disorders - Sindhu, Ravindran; Neoh, Siew Chin, Dr.; Muthusamy, Hariharan, Dr. (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/